2006
DOI: 10.1016/j.ydbio.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Long-range upstream and downstream enhancers control distinct subsets of the complex spatiotemporal Sox9 expression pattern

Abstract: SOX9 is an evolutionary conserved transcription factor that is expressed in a variety of tissues, with essential functions in cartilage, testis, heart, glial cell, inner ear and neural crest development. By comparing human and pufferfish genomic sequences, we previously identified eight highly conserved sequence elements between 290 kb 5' and 450 kb 3' to human SOX9. In this study, we assayed the regulatory potential of elements E1 to E7 in transgenic mice using a lacZ reporter gene driven by a 529 bp minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 58 publications
5
127
0
1
Order By: Relevance
“…Therefore, there must be at least one essential Rac-regulated transcriptional element far upstream or downstream of the transcription start site. In fact, the collagen promoter is known to have distant enhancers located 20 kb upstream of the transcription start site, 45,46 while genes like Bmp2 47 and Sox9 48 have enhancer elements hundreds of kb downstream of their promoters. Although the identification of the critical Rac-regulated factor(s) requires further study, we can now suggest a model of cyclin D1 gene regulation in MEFs: ERK activity induces mid-G 1 cyclin D1 gene expression independently of NFκB activity while Rac and NFκB signal in cooperative, but parallel, pathways to stimulate cyclin D1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there must be at least one essential Rac-regulated transcriptional element far upstream or downstream of the transcription start site. In fact, the collagen promoter is known to have distant enhancers located 20 kb upstream of the transcription start site, 45,46 while genes like Bmp2 47 and Sox9 48 have enhancer elements hundreds of kb downstream of their promoters. Although the identification of the critical Rac-regulated factor(s) requires further study, we can now suggest a model of cyclin D1 gene regulation in MEFs: ERK activity induces mid-G 1 cyclin D1 gene expression independently of NFκB activity while Rac and NFκB signal in cooperative, but parallel, pathways to stimulate cyclin D1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous report has indicated that the Sox 9 promoter region contained a binding site for LEF-1 [31], while another study showed direct regulation of Sox 9 expression by LEF-1 [32]. Based on such findings, we then sought to determine whether inhibiting LEF-1 via miR-449a would in turn translate into the proportional repression of Sox 9, and whether the opposite effect would be observed when a miR-449a antagomir was used.…”
Section: Figmentioning
confidence: 96%
“…Thus, Xenopus Snail-2 and mouse Sox-9 promoters were found to contain binding sites for the Lef/Tcf transcription factors, indicating direct regulation of their expression by the canonical Wnt signaling pathway. 202,203 In addition, both mouse Sox-9 and chick Sox-10 exhibit in their regulatory sequence enhancers that drive specifically precocious expression in cranial NC cells, thereby revealing the presence of unique gene regulatory networks in this particular NC population. 194,202 Interestingly, these enhancers contain binding sites for Ets-1, which is restricted to delaminating NC cells in the head.…”
Section: 211mentioning
confidence: 99%